Development Augmented Reality as a Learning Media for Sensory System Material for Class XI in Biology Learning - Yunita*, Yunita; Ariyanti, Nur Aeni; Faikhamta, Chatree (Universitas Syiah Kuala, 2025)
Biological material, one of which is the sensory system, whose objects are difficult to approach directly, requires more sophisticated learning media. This is because the sensory system learning process still uses 2D-based learning media which is difficult to display biological objects in real terms. Teachers and students need media that can visualize material well and can be accessed flexibly via smartphone. Technology AR, with its characteristics of being able to display objects in more detail in 3D and being able to be used on smartphones, could be a solution. This research aims to develop AR on human sensory system material. This research uses the ADDIE (analysis, design, development, implementation, and evaluation). Data collection was carried out through expert validation and implementation of student responses. The material expert validation results were 98.25% and the media expert validation results were 89.25% (very good category). The teacher assessment results were 96.75%, and student responses were 83.5% (very good category). Based on these results, it is known that the AR media developed is suitable for use in learning sensory system material in biology learning